Ethics in Islamic Markets: Exploring Their History and Impact on Islamic Civilization - Izzun Nisa’Yanayiroh; Khusnudin; Fadlil Abdani (al-Afkar, Journal For Islamic Studies, 2025)
Islamic markets have played a key role in the history of Muslim civilization, not only as economic centers but also as venues for the application of Islamic ethics in transactions. This article examines ethical principles such as honesty, fairness, and the prohibition of usury (riba) in the context of Islamic markets, from the early Islamic era to the golden age of the caliphate. Furthermore, it addresses the challenges of Islamic markets in the modern era, including the application of Sharia principles in the global and digital economy. This study uses a literature review method to collect, assess, and integrate various relevant literature sources, with the aim of gaining deeper insights into the topic discussed. These findings demonstrate the importance of maintaining ethical values in markets to achieve social justice and economic sustainability in the future.